New Insights Into the Cancer–Microbiome–Immune Axis: Decrypting a Decade of Discoveries - Jain, Tejeshwar; Sharma, Prateek; Are, Abhi C.; Vickers, Selwyn M.; Dudeja, Vikas (Frontiers in Immunology, 2021)
The past decade has witnessed groundbreaking advances in the field of microbiome research. An area where immense implications of the microbiome have been demonstrated is tumor biology. The microbiome affects tumor initiation and progression through direct effects on the tumor cells and indirectly through manipulation of the immune system. It can also determine response to cancer therapies and predict disease progression and survival. Modulation of the microbiome can be harnessed to potentiate the efficacy of immunotherapies and decrease their toxicity. In this review, we comprehensively dissect recent evidence regarding the interaction of the microbiome and anti-tumor immune machinery and outline the critical questions which need to be addressed as we further explore this dynamic colloquy.